100 Intravenous iron in symptomatic heart failure is safe and cost-effective. (17th July 2020) - Redfern, James; Hung, John; MacCarthy-Ofosu, Beverly; Goode, Rachel; Wallace, Valerie; Quarterman, Clare; Rao, Archana
Abstract : Introduction: Heart failure (HF) affects approximately 1 million people in the UK, adversely affecting quality of life, functional capacity and cognitive health. This results in frequent hospitalisation and significant healthcare costs1, 2. Iron deficiency complicates heart failure in approximately 50% of patients3, and is increasingly recognised as a significant contributor to morbidity in this group. Intravenous ferric carboxymaltose (FCM) has been shown to improve quality of life (New York Heart Association [NYHA] class and Kansas City Cardiomyopathy Questionnaire [KCCQ]), performance in 6-minute walk test (6MWT), reduce hospitalisations, and is reflected in international guidelines4-7. We aimed to assess the feasibility, safety and cost implications of establishing an IV iron service for patients with HF in a large tertiary cardiology centre. Method: Over a 6-month period (July-December 2019), outpatients with symptomatic heart failure (NYHA class ≥2) and severe left ventricular systolic dysfunction (LVEF ≤40%) were screened, and serum iron studies performed. Patients with iron deficiency (ferritin <100ug/mL or 100-300ug/mL and transferrin saturation [TSAT] <20%) were included and were excluded if polycythaemic (Hb ≥150g/L) or if there was evidence of active infection. A course of FCM was administered according to newly developed local protocols within the infrastructure of the existing IV iron service. Quality of life scores (NYHA and KCCQ) and serum measures of iron deficiency (Ferritin, TSAT, Hb) were compared at baseline and 12 weeks. All patients were monitored for anaphylaxis. The financial impact was calculated by subtracting the total cost of administration (day case admission, drug administration, staff time, consumables) from the received tariff. Results: Fifty-two patients underwent IV iron replacement (69% male, mean age 66 years) with no significant adverse events or hospital admissions. The financial impact to the trust was a net income of £55 per patient (FCM treatment £290, remuneration £345). Ferritin increased significantly 83.3ug/L to 433ug/L (p<0.0001) as did TSAT, 18% to 30% (p<0.0001) and Hb, 126g/L to 135g/L (p<0.01)[Figure 1 ]. Mean NYHA class and KCCQ scores were unchanged (2.5 to 2.3 [p=0.09] and 35-36 [p=0.68] respectively). Conclusion: Utilisation of the existing iron infusion service facilitated the delivery of IV iron replacement for patients with heart failure with little need for additional training and resources. Delivery of the service did not incur additional cost to the trust and in fact there was a small net gain. In-keeping with published data we demonstrated comparable improvements in serum iron parameters and a trend towards improvement in NYHA class. IV iron replacement with FCM is safe and affordable and should be considered in all iron deficient patients with symptomatic heart failure. Conflict of Interest: Yes - recieved honorarium from Vifor